INTEGRATIVE USE OF PENMAN-MONTEITH EQUATION WITH REMOTE SENSING AND GEOGRAPHICAL INFORMATION SYSTEM TECHNIQUES TO ESTIMATE EVAPOTRANSPIRATION VRIANCES IN IRAQ - & Abed Mohamed, Jawad (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This research was aimed to construct an integrative system which is capable of accurate determining and analyzing evapotranspiration rates in Iraq for long period , Since high evapotranspiration rates and extreme shortage in precipitation are the main causes of aridity, which considered principal reason for land degradation and land desertification eventually. FAO Penman-Monteith method was adopted because it's the international standard method. In this work meteorological readings of nine stations with comprehensive covering for Iraq's area were taken for every ten years in a long-term range (31 years). The daily evapotranspiration values had been calculated, then after the annual summation value determined for the years (1987, 1997, 2007, and 2017). The use of spatial analysis schemes proved that generally eighties decade of the last century had climax (Etr) values, then ETr rates rapidly decreased in whole Iraq except some anomalies. There were two reasons for this decrement, firstly air temperature value decent which increase relative humidity. Secondly wind speed rates falling (which considered the principal cause for reference evapotranspiration rates descending in this case).